Ethics briefing - Brannan, Sophie (Journal of medical ethics, 2021)
In June 2021, the BMA published its report on moral distress and moral injury in UK doctors.1 The report includes definitions of the terms ‘moral distress’ and ‘moral injury’ as well as a summary of how the concepts have developed over time. There is also an analysis of the BMA’s pan-profession survey of moral distress and moral injury of doctors in the UK, the first of its kind. The impact of COVID-19 and recommendations for tackling moral distress also feature.Many may be unfamiliar with the concepts of ‘moral distress’ and ‘moral injury’. These terms are relatively new, and debate is ongoing in academic circles on the best way to understand them.2 Some use the terms interchangeably. The BMA defines moral distress as the psychological unease generated where professionals identify an ethically correct action to take but are constrained in their ability to take that action. Even without an understanding of the morally correct action, moral distress can arise from the sense of a moral transgression. More simply, it is the feeling of unease stemming from situations where institutionally required behaviour does not align with moral principles. This can be as a result of a lack of power or agency, or structural limitations, such as insufficient staff, resources, training or time. The individual suffering from moral distress need not be the one who has acted or failed to act; moral distress can be caused by witnessing moral transgressions by others. Moral injury can arise where sustained moral distress leads to impaired function or longer-term psychological harm. Moral injury can produce profound guilt and shame, and in some cases also a sense of betrayal, anger and profound ‘moral disorientation’. It has also been linked to severe mental health issues.There is increasing recognition across the UK of the problem …